Evaluation of Metabolites and Amino Acids Assimilation by Yeast FT-858 in Saccharine Substrates for the Production of Bioethanolroduction - Larissa Pires Mueller; Maria do Socorro Mascarenhas Santos; Claudia Andrea Lima Cardoso; Margareth Batistote (Orbital: The Electronic Journal of Chemistry, 2019)
Yeasts are exposed to stressing agents in the fermentation process. The study aims to analyze the production of ethanol and intracellular glycerol, as well as to evaluate the consumption of amino acids by yeast FT-858 in different culture conditions. The sugarcane and sorghum broth were used, at 22ºBx and pH of 5.0. A 2% YPD medium was pre-inoculated, and 0.10 g of lyophilised yeast were inoculated, incubated at 30 °C for 12 hours at 250 rpm. Cells were recovered by centrifugation and reinoculated in the fermentation medium at 30 °C and 40 °C at 250 rpm, this procedure was conducted with cell recycles, and 4 mL aliquots were withdrawn for analysis. Quantification of glycerol was accomplished by cell lysis and enzymatic kit of triglycerides, ethanol by gas chromatography and amino acid analysis by high performance liquid chromatography. The results showed that intracellular glycerol production and ethanol concentration were inversely proportional due to stress factors. The highest amount of amino acids available was in sorghum broth, and the most assimilated by the yeast were: serine, arginine, alanine and tryptophan and the high temperature accelerated their consumption of them.DOI: http://dx.doi.org/10.17807/orbital.v11i4.1220